2006
DOI: 10.1016/j.physletb.2006.01.004
|View full text |Cite
|
Sign up to set email alerts
|

N-spheres in general relativity: Regular black holes without apparent horizons, static wormholes with event horizons and gravastars with a tube-like core

Abstract: We consider a way to avoid black hole singularities by gluing a black hole exterior to an interior with a tube-like geometry consisting of a direct product of two-dimensional AdS, dS, or Rindler spacetime with a two-sphere of constant radius. As a result we obtain a spacetime with either "cosmological" or "acceleration" (event) horizons but without an apparent horizon. The inner region is everywhere regular and supported by matter with the vacuum-like equation of state p r + ρ = 0 where p r = T r r is the long… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 24 publications
3
17
0
Order By: Relevance
“…It does not mean that such configurations have no physical sense. By contrary, in some situations it is the tubelike configurations which are placed to the forefront (for example, in the context of the problem of avoidance singularities [12], in investigating properties of phantom matter [14], etc.). However, in any case, they represent a special class of wormhole configurations which differ from the standard ones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It does not mean that such configurations have no physical sense. By contrary, in some situations it is the tubelike configurations which are placed to the forefront (for example, in the context of the problem of avoidance singularities [12], in investigating properties of phantom matter [14], etc.). However, in any case, they represent a special class of wormhole configurations which differ from the standard ones.…”
Section: Discussionmentioning
confidence: 99%
“…In principle, one can take a finite piece of this horn and glue it to the metric with dr dl > 0 on the right side and dr dl < 0 on the left side. In doing so, one can obtain so-called "null wormholes" (N-wormholes) [12]. Although inside the region where p r + ρ = 0 NEC is satisfied on the verge, gluing to the normal matter on the borders needs the presence of exotic material and we return to the situation under discussion with all corresponding difficulties.…”
Section: B Horn-like Configurationsmentioning
confidence: 98%
“…Let us note that wormholes with "tube-like" structure (and regular black holes with "tube-like" core) have been previously obtained within different contexts in refs. [41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Substituting again (48), (45) into the matching relations (41) --(43) we find for the wormhole parameters:…”
mentioning
confidence: 99%
“…In [9] gravastar solutions have been studied in a generalized (Reissner-Nordström) exterior and solutions of the model stemming from the original Mazur-Mottola model have been analyzed. Gravastar type solutions in the context of solutions to Einstein's equations with tube-like cores have also been recently considred [10]. Pioneering in-depth studies of spherically symmetric systems with deSitter asymptotics may be found in [11] - [14].…”
Section: Introductionmentioning
confidence: 99%